2005
DOI: 10.1677/joe.1.05980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leukemia inhibitory factor on 3T3-L1 adipocytes

Abstract: Leukemia inhibitory factor (LIF) is a member of the gp130 cytokine family and signals through the receptor complex of gp130 and the LIF receptor (LIFR) to activate the JAK/STAT signaling cascade. Since LIF activates STATs 1 and 3 in adipocytes, we examined the effects of LIF on 3T3-L1 adipocytes. Our studies clearly demonstrate that LIF treatment had minimal effects on adipocyte differentiation as judged by marker gene expression, but did inhibit triacylglyceride (TAG) accumulation during adipogenesis. Acute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that adipocytes in vitro and adipose tissue in vivo are responsive to gp130 cytokines (Balhoff and Stephens 1998;Stephens et al 1998;Lagathu et al 2003;Rotter et al 2003;Zvonic et al 2003Zvonic et al , 2004Tenney et al 2005;White et al 2008) and exert differential effects on adipogenesis. To date, no gp130 cytokines have been shown to promote adipogenesis, but as shown in Table 1, several cytokines in this family have been shown to inhibit adipocyte development (Keller et al 1993;Meng et al 2001;Zvonic et al 2003Zvonic et al , 2004Sopasakis et al 2004;Hogan and Stephens 2005;Miyaoka et al 2006;Song et al 2007;White et al 2008).…”
Section: Glycoprotein 130 (Gp130) Cytokinesmentioning
confidence: 99%
“…Liver homogenates were prepared in 25 mM sodium phosphate, 1 M NaCl, 1 mM EDTA pH 7.4,18 and triglyceride levels were determined using the Vitros DT60/DT60 II Chemistry System Bioanalyzer with Vitros TRG DT slides and DT calibrator Kit (Ortho-Clinical Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid extraction was performed using 100 L of the cell lysate mixed with 100 L of tertiary butanol and 50 L of a methanol:Triton X-100 mixture. 21 Aliquots of this extraction were then assayed in triplicate for total triglycerides using a triglyceride determination kit following the protocol of the manufacturer (Sigma TR0100).…”
Section: Lipid Extraction and Measurement Of Cardiac Triglyceridesmentioning
confidence: 99%